2013
DOI: 10.1111/his.12175
|View full text |Cite
|
Sign up to set email alerts
|

EGFR expression and copy number changes in low T‐stage oral squamous cell carcinomas

Abstract: Only a small subgroup of early oral SCC is characterized by EGFR amplification, which can be identified reliably using EGFR-SISH technology. This finding suggests that EGFR gene amplification mostly occurs in advanced stages of oral SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
5
9
0
1
Order By: Relevance
“…This is consistent with data from studies of EGFR GCN in OSCC, which indicate that EGFR genomic gain is a late event in oral carcinogenesis (23)(24)(25). It is striking, however, that the majority of OPMD with low polysomy progressed to OSCC.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is consistent with data from studies of EGFR GCN in OSCC, which indicate that EGFR genomic gain is a late event in oral carcinogenesis (23)(24)(25). It is striking, however, that the majority of OPMD with low polysomy progressed to OSCC.…”
Section: Discussionsupporting
confidence: 89%
“…This finding was consistent across both the early-stage and transformed OSCC groups. It is higher than the 9% rate reported in a tissue-microarray study by R€ ossle and colleagues (24). This earlier study also focused on early-stage (stage I/II) OSCC; however, it was limited by assessment of 0.6 mm diameter tissue cores.…”
Section: Cancer Epidemiol Biomarkers Prev; 25(6) June 2016mentioning
confidence: 75%
See 1 more Smart Citation
“…Regarding evaluation of EGFR, authors such as Rössle et al 6 and Rajesweri et al 28 and the authors of this study found that in all the samples analyzed, regardless of diagnosis, immunostaining of EGFR was always positive. However, there were variations in its intensity range.…”
Section: -2627supporting
confidence: 50%
“…5 Its mutation stimulates mitosis and inhibits the apoptosis of neoplastic keratinocytes. 6 This receptor is expressed both in normal epithelia and in those subjects with pathologies such as epithelial dysplasia and carcinomas, where proliferation and differentiation of keratinocytes are altered.…”
Section: 4mentioning
confidence: 99%